Pengaruh Persepsi Harga dan Suasana serta Kualitas Pelayanan terhadap Keputusan Konsumen Makan pada Rumah Makan Bebek Pawon di Samarinda - Gajali Rahman; Suharno Suharno; Asnawati Asnawati (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2018)
Influence Perception of Price and Atmosphere And Service Quality Decision Against Eating Lunch At pawon Duck 'in Samarinda  The purpose of this study to determine the perception of price and Atmosphere And Service Quality Decision Against Eating Lunch At pawon Duck 'in Samarinda. The theoretical basis used by management pemasaram by using multiple linear regression analysis with 60 samples. The conclusion of this study: Price has a significant influence on consumer decisions at home feeding the ducks pawon, thus the research hypothesis is accepted. The atmosphere has a significant influence on consumer decisions at home feeding the ducks Pa Won. thus the research hypothesis is accepted. Quality of service has a significant influence on consumer decisions at home feeding the ducks pawon, thus the research hypothesis is accepted.